Liquidity risk management and credit supply in the financial crisis - Cornett, Marcia Millon; McNutt, Jamie John; Strahan, Philip E.; Tehranian, Hassan (Journal of Financial Economics, 2011)
Liquidity dried up during the financial crisis of 2007–2009. Banks that relied more heavily on core deposit and equity capital financing, which are stable sources of financing, continued to lend relative to other banks. Banks that held more illiquid assets on their balance sheets, in contrast, increased asset liquidity and reduced lending. Off-balance sheet liquidity risk materialized on the balance sheet and constrained new credit origination as increased takedown demand displaced lending capacity. We conclude that efforts to manage the liquidity crisis by banks led to a decline in credit supply.